TEACHING STRATIFICATION WITH CRAYONS - Wetcher-Hendricks, Debra; Luquet, Wade (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Lessons on social stratification present challenges for both sociology teachers and students. As students tend to be acquainted primarily with the lifestyle to which they have been raised, they often have little understanding of the widespread effects of social inequality. The exercise described in this article attempts to expose students to some of these effects. The professor creates a stratified classroom by distributing crayon packs of various sizes. Students then use the crayons that they have been allotted to draw a picture. As students realize that the quality of the picture depends to a great extent upon the crayons that they received, they gain an appreciation for the ramifications of social inequality. In addition to gaining experiential knowledge about the basis of social inequality, students who take part in the exercise express significantly more satisfaction with the method of instruction than do those taught by more traditional methods.